Hb Kalundborg [β79(EF3)Asp→Glu; HBB: c.240C>a], a Possible Low-affinity Hemoglobin Variant Detected during Hb A1c Measurement. (4th March 2022) - Ahmad-Nielsen, Emil B.; Szecsi, Pal B.; Bratholm, Palle S.; Petersen, Jesper; Glenthøj, Andreas
Abstract: A previously unknown hemoglobin (Hb) variant was detected during measurement of glycosylated Hb (Hb A1c ) after the introduction of a new high performance liquid chromatography (HPLC) apparatus. Subsequent DNA sequencing revealed a heterozygous single nucleotide substitution at codon 79 (C>A) on the β-globin gene changing an amino acid [β79(EF3)Asp→Glu; HBB : c.240C>A]. The new Hb variant was named Hb Kalundborg after the place of origin of the proband. Heterozygosity for this mutation appears to have no clinical significance in itself except for a possibly slightly lower oxygen affinity. However, it interferes with Hb A1c measurement by HPLC, causing a falsely high Hb A1c concentration when using the G11 apparatus with clinical implications possibly to follow.